SINGKRONISASI PERATURAN KOMISI PEMILIHAN UMUM NOMOR 12 TAHUN 2015 DENGAN UNDANG-UNDANG NOMOR 8 TAHUN 2015 TENTANG PEMILIHAN GUBERNUR, BUPATI, DAN WALIKOTA (Fakultas Hukum Dehasen, 2019)
The purpose of this study was to find out, understand, and analyze in depth the synchronization of General Election Commission Regulation Number 12 of 2015 with Law Number 8 of 2015 concerning the election of governors, regents and mayors and the validity of registration of candidates for regional heads by two political party general election commission in accordance with applicable laws and regulations. This study uses a normative juridical method that is focused on reviewing the rules or norms in positive law with a statutory approach and a conceptual approach. Then this legal material is analyzed qualitatively, the problems are analyzed by interpreting all laws and regulations relating to the issues discussed, evaluating legislation, and assessing legal materials by taking into account legal theories, research results, and the opinions of legal experts. . From this analysis shows that there is an inconsistency between the General Election Commission Regulation Number 12 of 2015 and Law Number 8 of 2015. In the event of inconsistencies between laws and regulations, then the principle of Lex Superiori derogat Legi Inferiori is applicable, namely higher legislation overrides lower legislation. The validity of the registration of candidates for regional heads by two political party management is invalid because the decision to determine the candidates for regional heads by the two political parties by the electoral commission does not meet the requirements for the validity of state administrative decisions. Keywords: Synchronization, Legality, General Election Commission, State Administration Decision, Regional Head Candidates